Making projects sing : a musical perspective of project management - Sivaraman, Raji. (Portfolio and project management collection., 2016)
This book explores project management (PM) from a musical perspective. Seeking ways of understanding PM in musical ways, distinctive approaches to the management of risk, experimentation, the conception and practice of teams, and the realization of imagination, are explored to highlight both the synergies and distinctions between musical practice and project management in the wider corporate and industrial sectors. The intention being to surface insights of value, capable of adaptation and practical application in a range of contexts, a series of conceptual models and thinking exercises are presented, each designed to structure a more musical approach to project management and capable of application at every scale of project management, and every possible project management environment. The contention of this book is that music provides an interesting context through which to consider project management practice, and therefore a unique opportunity to approach project management from both a different viewpoint and a different mindset. Music is a vibrant field of activity incorporating distinctive approaches to the development and maintenance of expertise, the transfer of knowledge, and the realization of remarkable cultural creativity. Synergies between musical practice and the wider project management profession are many and varied, and more musical approaches to project management may not only be possible, but may also be an engaging means of developing creativity in project outcomes.